Utilization of the River for Crossing Business by Taeng Village Communities in Gowa Regency - Ardiansyah Basir; Kahar Lahae; Muhammad Aswan (LEGAL BRIEF, 2023)
The research objective to analyze permits for the use of rivers used as crossing businesses and analyze and analyze the responsibilities of ferry service managers to users of crossing services in the event of an accident. The research used the empirical legal research, is a type of of legal research that functions to be able to see the law in a real sense. Sources of data were obtained through primary and secondary sources, as well as interviewing the Head of the Pompengan Jeneberang River Basin Office, the Head of the River, Lake and Ferry Transportation Office and the Crossing Business Owner in Taeng Village. This research was then analyzed qualitatively after the data analysis was completed, the results were presented descriptively.The research result indcates that the responsibility of the manager of the ferry service to the user of the ferry service in the event of an accident has 3 responsibilities, the first is civil responsibility on the basis of acts against law, the second is the responsibility of the carrier in the event of damage resulting from the transportation and moral responsibility and legal protection provided preventive and repressive.